Separation efficiency of a wastewater bar screen based on a 3D computational fluid dynamics modeling - En-Nabety, Loubna; Boudi, El Mostapha (Desalination and water treatment, 2024)
The wastewater screening process is a crucial step in the majority of wastewater treatment plants, frequently using mechanical bar screens as the first filtration step to remove heavy debris from the wastewater flow. In the present study, two 3D geometries of bar screens with different screen openings were presented to investigate the effect of the variation in screen spacing of bars on the separation efficiency of debris. Based on the Ansys Fluent CFD code within the Eulerian-Lagrangian approach, the particle trajectories were tracked, and the retention efficiency of these two bar screens was evaluated. The results show that a higher particle separation efficiency is favored for small bar spacing and coarse particle sizes. Actually, despite the impact of bar spacing on the separation efficiency of particles, the adequate choice of this parameter is related to particle properties and the fluid flow inlet velocity. These parameters also have a great influence on the separation efficiency of bar screens. The study can help for more structural improvements in the shape of the screening media, which leads to enhanced performance of wastewater screening facilities. [Display omitted] •Two wastewater bar screens were examined using CFD modeling with particle tracking.•Bar spacing and particle size affect the efficiency of wastewater bar screens.•High separation efficiency occurs for small bar spacing and coarse particle size.•Solid properties and fluid inlet velocity impact particle separation efficiency.•CFD with particle tracking is an efficient tool for enhanced wastewater screening.